Determinação da idade e crescimento da tainha Mugil liza Valenciennes, 1936 no sistema lacunal costeiro tropical Mundaú – Manguaba, Alagoas - Sousa, Marcia Ferreira de (2013)
Seasonality in tropical environments is mainly characterized by changes in rainfall. In tropical estuaries is primarily characterized by seasonal variations in chlorophyll-a and suspended matter, these are more abundant in the rainy season, increasing the productivity of these ecosystems and, more specifically, providing food for mullet species. The lebranche M. liza is one of the most species exploited by fisheries in Alagoas. Added to these factors the dearth of studies on age and growth in tropical regions, makes resource management based on technical and scientific bases hindered. The main objectives of this thesis are: a) identify which biotic and abiotic factor is related to the seasonal rhythm of growth of M. liza on Lagoon estuary and Mundaú; (b) to estimate the parameters of von Bertalanffy growth, age limit (t0.95) natural mortality (M) and understand the dynamics of the life cycle of M. liza in the estuary of Lagoa Mundaú - Alagoas, Brazil. For this purpose, monthly samples were taken (between July/11 Jun/12) in the estuary of Lagoa Mundaú. We collected 553 individuals with total length (Lt) between 7 and 78 cm. The females were lower (Ltmean=45.69 ± 12.65 cm) than males (Ltmean= 47.86 ± 9.54). Analysis of relative marginal increment (RMI) in the marks deposited in otoliths of M. liza indicates a significant decrease in the growth rate in August, consequence of a slow-growing brand year, coinciding with the period reproductive adults, high rainfall (211 ± 94) and low salinity (3.49 +0.05) in a estuary. Young fish in the growth rate decreases during the dry season (Dec-Feb) caused by low oxygen availability. The growth parameters estimated to M. liza, constitute the first estimated values for the species in the tropics as: L ∞ (cm) = 71 cm; k = (years-1) = 0.28; t0 (years) = -0.14 (age groups of 1-8); longevity (A0, 95 = 10.6) years and M = 0.28. M. liza is therefore regarded as a species of moderate to rapid growth rate, with a relatively low longevity and a high natural mortality rate, compared to other species of Mugilidae. These results corroborate with obtained for the same species in subtropical regions, but differ from the parameters obtained in temperate regions. In this context, this study can serve as a basis for management of the species in that estuary.